Floristic studies on Lycophytes and Ferns of Ulandy and Pollachi Range of Anamalai Tiger Reserve - Johnson, M.; Shivananthini, B.; Silvia Juliet, I.; George, Vidyarani; Anwardeen, I.; Ramasubramanian, S.; Ganeshan, M.G.; Chakravarthi, Peter Prem J. (Indian Forester, 2024)
The present investigation was carried out to enumerate the lycophytes and ferns of Ulandy and Pollachi range of Anamalai Tiger Reserve (ATR), Southern Western Ghats, India. Fourty seven species of pteridophytes are recorded in the Ulandy range belonging to fourteen families and twentyseven genera. Twenty-four species of pteridophytes belonging to eleven families and eighteen genera are recorded in the pollachi range. Among the observed families, Pteridaceae are dominant pteridophytes in the Ulandy and Pollachi range of ATR with 11 species. Among the 47 observed species, 16 species are terrestrial, 14 species are lithophytes, 11 species are epiphytes, 6 species are Sciophytes, 2 species are riverine in the ulandy range. Of which Among the 24 observed species, 21 species are terrestrial, 11 species are lithophytes, 2 species are Epiphytes, 2 species are xerophytes and 1 species is Merophyte in the pollachi range. Among observed species, 37 species showed various ethnobotanical activities.